DNA damage, serum metabolomic alteration and carcinogenic risk associated with low-level air pollution. (15th March 2022) - Xu, Jiayu; Liu, Yu; Zhang, Qiaojian; Su, Zekang; Yan, Tenglong; Zhou, Shupei; Wang, Tiancheng; Wei, Xuetao; Chen, Zhangjian; Hu, Guiping; Chen, Tian; Jia, Guang
Abstract: Outdoor air pollution has been classified as carcinogenic to humans (Group 1) for lung cancer, but the underlying mechanism and key toxic components remain incompletely understood. Since DNA damage and metabolite alterations are associated with cancer progression, exploring potential mechanisms linking air pollution and cancer might be meaningful. In this study, a real-time ambient air exposure system was established to simulate the real-world environment of adult male SD rats in Beijing from June 13th, 2018, to October 8th, 2018. 8-OHdG in the urine, γ-H2AX in the lungs and mtDNA copy number in the peripheral blood were analyzed to explore DNA damage at different levels. Serum non-targeted metabolomics analysis was performed. Pair-wise spearman was used to explore the correlation between DNA damage biomarkers and serum differential metabolites. Carcinogenic risks of heavy metals and PAHs via inhalation were assessed according to US EPA guidelines. Results showed that PM2.5 and O3 were the major air pollutants in the exposure group and not detected in the control group. Compared with control group, higher levels of 8-OHdG, mtDNA copy number, γ-H2AX and PCNA-positive nuclei cells were observed in the exposure group. Histopathological evaluation suggested ambient air induced alveolar wall thickening and inflammatory cell infiltration in lungs. Perturbed metabolic pathways identified included glycolysis/gluconeogenesis metabolism, purine and pyrimidine metabolism, etc. γ-H2AX was positively correlated with serum ADP, 3-phospho-D-glyceroyl phosphate and N-acetyl-D-glucosamine. The BaPeq was 0.120 ng/m 3 . Risks of Cr(VI), As, V, BaP, BaA and BbF were above 1 × 10 −6 . We concluded that low-level air pollution was associated with DNA damage and serum metabolomic alterations in rats. Cr(VI) and BaP were identified as key carcinogenic components in PM2.5 . Our results provided experimental evidence for hazard identification and risk assessment of low-level air pollution. Graphical abstract: Image 1 Highlights: Low-level air pollution could induce genetic damage and lung injury. Low-level PM2.5 and O3 remarkably altered the serum metabolome profile. Low-level air pollutants may still increase carcinogenic risk. Cr(VI) and BaP was identified as key carcinogenic components in atmospheric PM2.5 .